Comparison of Efficacy of Localized Narrow-Band UVB Therapy Versus Localized PUVA Therapy in Chronic Hand Eczema - Dhan Keshar Khadka; Sudha Agrawal; Arpana Rijal; Samir Shrestha (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Hand eczema is a type of dermatitis largely confined to the hands. Narrowband UVB (NBUVB) appears to be as effective as topical PUVA therapy in the treatment of chronic hand dermatitis. However, the risks of phototoxicity and dyspigmentation associated with local PUVA therapy make NBUVB therapy a preferable initial therapeutic option.